Pemberdayaan UMKM Dekpid melalui Pembimbingan Promosi melalui Instagram dan Desain Packaging Produk - Andita, Mirza Putri; Indra, Azalia Mawarindani; Yunifa, Wiza; Handra, Fathya Salsabilla (Jurnal Pemberdayaan Umat, 2024)
Purpose: This activity aims to assist small business, Dekpid, in creating attractive packaging and enhancing the quality of its social media content. Methodology/approach: This project follow a practical approach, using interview techniques to identify challenges faced by Dekpid and to develop the activities or programs for solving them. Ultimately, the project assists Dekpid in utilizing social media to enhance the promotion of their products through higher-quality content and provides guidance on creating packaging designs. Results/findings: The output of the activity contributes to an enhanced understanding of designing product packaging and the development of high-quality social media content to support the promotion of SMEs Dekpid on Instagram. Conclusion: Lecturers and undergraduate students are participating in initiatives aimed at boosting the competitiveness of UMKM Dekpid. These activities include the development of creative packaging designs that align with the logo, as well as the development of social media marketing content to promote the products. Limitation: One limitation of the activity was the restricted timeframe, which led to the project concluding in less than a month, resulting in a less detailed impact and a potential for better outcomes if it had a longer duration. Contribution: These program can help the growth of Dekpid as one of small businesses in Palembang. Ultimately, this growth is expected to lead to an increase in job opportunities within the area.